Assessing the effectiveness and pathways of planned shelters in protecting mental health of flood victims in China. (3rd December 2020) - Zhong, Shuang; Pang, Minghui; Ho, Hung Chak; Jegasothy, Edward; Clayton, Susan; Wang, Zhe; Huang, Cunrui
Abstract: Background. Evacuation and sheltering are commonly used strategies for disaster risk reduction and climate change adaptation, but may negatively affect mental health of internally displaced persons (IDPs). Recently, Chinese governments have developed planned settlements providing integrated and intensive health services and environmental interventions to reduce immediate disastrous impacts and support the mental health of IDPs. Methods. Here we selected 69 planned shelters by stratified sampling to describe the implemented interventions conducted in Anhui Province of China after the 2016 severe floods, and we used standardized psychological scales to survey the intervention group (IDP who lived in these planned shelters) and the matched control group (victims living in their homes). Multivariable logistic regression was used to examine the association between social-demographic characteristics, flooding exposure, environmental conditions and the psychological diseases. Adjusted odds ratios (ORs) were calculated to compare their prevalence of psychological diseases, and to identify its influencing factors though comparing multiple interventions. Finally, the structural equation modeling was used to identify their influencing pathways. Results. Compared with the control group, the intervention group had a significantly lower risk of anxiety (OR = 0.36; 95% CI: 0.18–0.71), depression (OR = 0.36; 95% CI: 0.19–0.68) and post-traumatic stress disorder (OR = 0.29; 95% CI: 0.15–0.56). Environmental interventions providing clean water, safe food, environmental hygiene, risk communication and sufficient accommodation had a protective effect (standardized indirect effect = −0.153, p < 0.01) on the risk of psychological problems, mediating the negative effect caused by displacement and sheltering. Conclusions. How planned shelters were used to achieve better mental health outcomes in Anhui could inform other flood-prone areas to mitigate psychological vulnerability of IDPs.